Effect of F Dopant on the Structural Stability, Redox Mechanism, and Electrochemical Performance of Li2MoO3 Cathode Materials. (1st October 2020) - Teng, Rui; Yu, Hai‐Tao; Guo, Chen‐Feng; Xie, Ying; Yi, Ting‐Feng
Abstract: F‐doped Li2 MoO3 (LMOF) nanosheets are successfully prepared by a facile method. The X‐Ray powder diffraction, scanning electron microscopy, and transmission electron microscopy results show that the thickness of the Li2 MoO3 sheets decreases gradually with increasing F doping amount, while the interlayer spacing along the z ‐axis increases. The X‐ray photoelectron spectroscopy and cyclic voltammetry results indicate that F doping is helpful for suppressing the irreversible phase transformation and the formation of Li2 MoO4, and the relevant redox mechanism is discussed. Moreover, density functional theory calculations demonstrate that F‐doped samples exhibit a higher structural stability, which is important for the improvement of the electrochemical performance. The initial discharge capacities are 228.97, 229.74, 232.99, 238.07, and 250.07 mAh g −1, respectively for the LMOF‐0, LMOF‐1, LMOF‐3, LMOF‐5, and LMOF‐7 samples. LMOF‐5 has the best performance, and it can deliver a specific capacity of 96.1 mAh g −1 at the 500th cycle at a charge/discharge current density of 1020 mA g −1 . The experiments identify the promising role of anion doping and offer some important information for the design and optimization of Li2 MoO3 ‐based cathode materials. Abstract : F‐doped Li2 MoO3 materials are successfully synthesized through a facile molten salt method. The introduction of F dopants improves the structural stability and leads to a different redox mechanism, that is responsible for the excellent cycle stability and rate performance of the materials. This work has significance for the design and optimization of Li2 MoO3 ‐based cathode materials.